THE CONVERSATIONAL STYLES BY MALE AND FEMALE SELLERS IN BUSINESS TRANSACTIONS AT TRADITIONAL MARKET “PASAR SENTOSA BARU” MEDAN - Diana Hayati Pulungan; Sumarsih Sumarsih; Didik Santoso (LINGUISTIK TERAPAN, 2018)
This research deals with the conversational styles by male and female sellers in business transactions at traditional market “Pasar Sentosa Baru” Medan. It was conducted using qualitative research design. The subjects of 8 persons namely 4 male sellers and 4 female sellers were taken which they produced 20 conversations for each genders. The ages ranged from 30 to 60 years old. They come from various sellers, namely fish, chicken, vegetables, fruits, and spice. The instruments of collecting data were observation, recording, field notes, and interviewing adopted by Miles, Huberman, and Saldana (2014). The findings show that there were five types of conversational styles used by male and female sellers. In conversational styles used by male sellers; amount of talk (30%), interruption (26.7%), conversational support (21.7%), compliment (16.6%), and tentativeness (5%). In conversational styles used by female sellers; interruption (29%), amount of talk (23%), conversational support (24%), tentativeness (15%), and compliment (9%). In conversational styles in male sellers business transaction, the more dominant responses refer to talk of amount because they talk much in interaction in public context, while for female, the more dominant responses refer to interruption because the female sellers are taken as a violation and a sign of conversational dominance.Keywords: Conversational styles, Gender, Traditional Market.